A cross-sectional analysis for exploring the challenges of faculty Development Programmes at a newly developed medical college - Rabia Aftab; Aun Ali (Journal of the Pakistan Medical Association, 2025)
There is a need to relaunch Faculty Development Programmes (FDPs) in order to satisfy the demands, meet the challenges and requirements of medical education, and to train a new group of qualified faculty members, researchers, educators, and professionals. This study aims to explore the challenges to the faculty development programme at a newly developed medical college. A descriptive cross-sectional study design was employed for this research. The questionnaire used in the study for data collection was divided into four sections: 1) Institution related, 2) Personal related, 3) Curriculum-related, and 4) Student and research related. After analysing the collected data, it is evident that budget constraints were the most common challenges faced by the faculty members. Other challenges were lack of reward for teaching, fragmented structures of the FDP, and paucity of research. There should be institutional policies to arrange adequate resources, align FDP parallel to other educational activities, provide research platforms and initiate rewards systems for faculty members. Keywords: Challenges, Faculty, Medical education, Reward.